Topical Medicine Potency of Musa paradisiaca var. sapientum (L.) kuntze as Oral Gel for Wound Healing: An In Vitro, In Vivo Study - Budi, Hendrik Setia; Anitasari, Silvia; Ulfa, Ninik Mas; Juliastuti, Wisnu Setyari; Aljunaid, Mohammed; Ramadan, Doaa Elsayed; Muzari, Koko; Shen, Yung-Kang (European Journal of Dentistry, 2022)
Objective Topical application of ambonese banana (Musa paradisiaca var. sapientum (L.) kuntze) stem sap gel (GEGPA) on the socket wound area showed an increase in the expression of platelet-derived growth factor-BB, while decrease in the expression of matrix metalloproteinase-2 and 9. The aim of this study is to achieve standard formulation of GEGPA through stability, viscosity, distribution area, and drugs release for oral gel wound healing.Materials and Methods This is an in vitro and in vivo study with the randomized posttest only control group design. The gel was formulated according to the composition of each group by adding hydroxypropyl methylcellulose (HPMC), Lexgard, propylene glycol, and cold water to obtain 100 g of gel. Observations were made through the following tests: stability, viscosity, distribution area, drug release, and histopathological analysis of tooth extraction wound healing.Statistical analysis Data were analyzed using a one-way analysis of variance (α = 0.05) with GraphPad Prism-8 statistical software.Results The study showed that the GEGPA formulation was stable against changes in consistency, color, smell, homogeneity, and pH value. There is a significant difference between groups with respect to viscosity (p = 0.0001), adhesion (p = 0.004), dispersion (p = 0.000), and fibroblast cell numbers on days 3 and 5 (p = 0.007 and p = 0.001). There is no interaction between the active ingredients and the gel base of all formulations. Formulation 3 had better properties in terms of viscosity, broad distribution, and drug release compared with other groups. Application of GEGPA to tooth extraction wounds showed a significant proliferation of fibroblast cells on days 3 and 5.Conclusions The formulation of M. paradisiaca var. sapientum (L.) kuntze extract with HPMC and propylene glycol obtained a gel preparation, GEGPA, that was organoleptically stable and met the topical gel standard for wounds in the oral cavity.
Keywords: drug compounding; drug stability; health risk; oral gel; wound healing